Desulfovibrio fairfieldensis adhesion on implantable titanium used in odontology: a preliminary study - Tchinda, Alex; Pierson, Gaël; Chezeau, Laetitia; Kouitat-Njiwa, Richard; Rihn, Bertrand Henri; Bravetti, Pierre (Cellular and Molecular Biology, 2021)
The study presented here aimed to assess the ability of Desulfovibrio fairfieldensis bacteria to adhere to and form biofilm on the structure of titanium used in implants. D. fairfieldensis was found in the periodontal pockets in the oral environment, indicating that these bacteria can colonize the implant-bone interface and consequently cause bone infection and implant corrosion. Plates of implantable titanium, of which surfaces were characterized by scanning electronic microscopy and Raman spectroscopy, were immersed in several suspensions of D. fairfieldensis cells containing potassium nitrate on the one hand, and artificial saliva or a sulfato-reducing bacterial culture medium on the other hand. Following various incubation timepoints bacteria were counted in different media to determine their doubling time and titanium samples are checked for and determination of the total number of adhered bacteria and biofilm formation. Adhesion of D. fairfieldensis on titanium occurs at rates ranging from 2.105 to 4.6.106 bacteria h-1cm-2 in the first 18 h of incubation on both native and implantable titanium samples. Following that time, the increase in cell numbers per h and cm2 is attributed to growth in adhered bacteria. After 30 days of incubation in a nutrient-rich medium, dense biofilms are observed forming on the implant surface where bacteria became embedded in a layer of polymers D. fairfieldensis is able of adhering to an implantable titanium surface in order to form a biofilm. Further studies are still necessary, however, to assess whether this adhesion still occurs in an environment containing saliva or serum proteins that may alter the implant surface.